Conceptualizing sustainability and resilience in value chains in times of multiple crises—Notes on agri-food chains - Alexander Follmann; Peter Dannenberg; Nina Baur; Boris Braun; Grit Walther; Amelie Bernzen; Jan Börner; Michael Brüntrup; Martin Franz; Linde Götz; Anna-Katharina Hornidge; Carolin Hulke; et al. (Die Erde : Journal of the Geographical Society of Berlin, 2024)
Global and regional agri-food value chains feed societies and are an income source for hundreds of millions of farmers around the world. They are also target areas for action to achieve a global sustainability transformation. Agri-food chains are highly vulnerable in the context of multiple crises, including the global environmental crisis, geopolitical fragmentation, armed conflicts and wars, and the aftermath of the COVID-19 pandemic. Measures to increase chain resilience are widely discussed; however, some such measures contradict sustainability measures. While there has been considerable research on the sustainability and resilience of agri-food chains, few studies have integrated both perspectives or outlined potential synergies and trade-offs. Therefore, this interdisciplinary literature review sketches possible contours for a synthesized research agenda on sustainability and resilience for agri-food chains during multiple crises. We argue that such an agenda should include, amongst others, a more differentiated and critical perspective on the importance of value chain characteristics and developments (e.g., power structures, capabilities, up- and downgrading, and the borders of chain internalities and externalities) a more comprehensive perspective that includes global and regional contexts and relations (e.g., whole-chain perspectives that integrate agro-input supply) an actor-oriented approach that interrogates aspects of inequality, cost-sharing, and the potential benefits of sustainability and resilience for different actors along a value chain (i.e., sustainability and resilience for whom?)
Keywords: 630; agriculture; global value chains; global production networks; supply chains; sustainability; resilience